2011
DOI: 10.1007/s12239-011-0068-y
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and challenges of controlling a LED AFS (adaptive front-lighting system) using fuzzy logic

Abstract: The vehicular illumination system has undergone considerable technological advances in recent decades such as the use of a Light Emitting Diode (LED) Adaptive Front-lighting System (AFS), which represents an industry breakthrough in lighting technology and is rapidly becoming one of the most important innovative technologies around the world in the lighting community. This paper presents AFS control alternatives using fuzzy logic (types 1 and 2) to determine its operating parameters taking into consideration t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…48 The study concluded that the fuzzy controller excellently executed the parameters set for control. In another study, Lukacs et al 49 presented adaptive front light system (AFS) control alternatives using fuzzy logic (types 1 and 2) to determine operating parameters, considering road conditions in the state of Sa˜o Paulo, Brazil. The fuzzy logic control technique, or modeling strategy, proved valuable when making multi-parameter decisions or decisions based on human knowledge.…”
Section: Overview Of Fuzzy-logic-based Control Approachmentioning
confidence: 99%
“…48 The study concluded that the fuzzy controller excellently executed the parameters set for control. In another study, Lukacs et al 49 presented adaptive front light system (AFS) control alternatives using fuzzy logic (types 1 and 2) to determine operating parameters, considering road conditions in the state of Sa˜o Paulo, Brazil. The fuzzy logic control technique, or modeling strategy, proved valuable when making multi-parameter decisions or decisions based on human knowledge.…”
Section: Overview Of Fuzzy-logic-based Control Approachmentioning
confidence: 99%
“…He k + Figure 6 The principle of the preview control of the headlamp bending angle According to the preview control algorithm [20] of the headlamp bending angle, AFS control unit is established, main modules include: preview control algorithm module, stepper motor module, feedback correction module and fuzzy module [21][22][23][24] .…”
Section: Simulation Of Preview Control Model a Simulation Model mentioning
confidence: 99%
“…Metalumen will be designing their products to meet the customer's requirements and will therefore have control over the products' specifications and will allow them to utilize the customization capabilities that they are renowned for. In this same sense, they will have full control of their own processes and will be able to ensure that the quality of their product and the customer service that goes along with it is up to their domestic standards (Lukacs et al 2011). …”
Section: Costsmentioning
confidence: 99%